Peak Bone Mass. The Role of Heredity and Modifiable Factors - Taciser Kaya; Rezzan Günaydın (Galenos Yayinevi, 2003)
Osteoporosis is a metabolic bone disease that is characterized by low bone mineral density and increase in fragility of bone. Low peak bone mass has been considered as a risk factor for osteoporosis. Heredity, physical activity level and diet are of importance in the determination of variations in peak bone mass. Investigations have been continuing on numerous candidate genes playing a role in the genetic programming of peak bone mass. It has been suggested that heredity may account for about 50-85% of the variation in peak bone mass. However, negative consequences of genetic factors may be changed by the modification of some environmental factors such as diet and physical activity.